2005
DOI: 10.1007/978-3-540-31843-9_7
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Labeling: Models and Efficient Algorithms for Rectangular Maps

Abstract: Abstract. In this paper, we present boundary labeling, a new approach for labeling point sets with large labels. We first place disjoint labels around an axis-parallel rectangle that contains the points. Then we connect each label to its point such that no two connections intersect. Such an approach is common e.g. in technical drawings and medical atlases, but so far the problem has not been studied in the literature. The new problem is interesting in that it is a mixture of a label-placement and a graph-drawi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
126
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(126 citation statements)
references
References 12 publications
0
126
0
Order By: Relevance
“…They also showed that the problem of maximizing the size of the rectangular equal-width labels of the sites on a horizontal line with top or bottom edges coinciding with the input line under the 4S model can be solved in O(n 2 log n) time. Labeling where the labels are connected to their associated features by leaders has so far been studied in the map labeling literature by Bekos et al [4,5,7], Fekete and Plaisant [10], Freeman et al [12], Müller and Schödl [23] and Zoraster [29]. Our labeling model is quite similar to the boundary labeling model proposed by Bekos et al [7].…”
Section: Related Literaturementioning
confidence: 73%
See 2 more Smart Citations
“…They also showed that the problem of maximizing the size of the rectangular equal-width labels of the sites on a horizontal line with top or bottom edges coinciding with the input line under the 4S model can be solved in O(n 2 log n) time. Labeling where the labels are connected to their associated features by leaders has so far been studied in the map labeling literature by Bekos et al [4,5,7], Fekete and Plaisant [10], Freeman et al [12], Müller and Schödl [23] and Zoraster [29]. Our labeling model is quite similar to the boundary labeling model proposed by Bekos et al [7].…”
Section: Related Literaturementioning
confidence: 73%
“…Labeling where the labels are connected to their associated features by leaders has so far been studied in the map labeling literature by Bekos et al [4,5,7], Fekete and Plaisant [10], Freeman et al [12], Müller and Schödl [23] and Zoraster [29]. Our labeling model is quite similar to the boundary labeling model proposed by Bekos et al [7]. In boundary labeling, the labels are placed on the boundary of a rectangle R (referred to as enclosing rectangle), which encloses the set of sites, and they are connected to their associated sites by non-intersecting leaders.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Boundary labeling was developed by Bekos et al [2] as a framework and an algorithmic response to the poor quality (feature occlusion, label overlap) of specific labeling applications. In boundary labeling, labels are placed at the boundary of a rectangle and are connected to their associated features via arcs referred to as leaders.…”
Section: Introductionmentioning
confidence: 99%
“…Bekos et al use rectilinear leaders with up to two bends. They study settings with labels arranged on one, two, or four sides of the bounding box of the illustration [5], in multiple stacks to the left [3], or where the objects to be labeled are polygons rather than points [4]. The optimization criteria that they consider are minimizing the total length and minimizing the total number of bends.…”
Section: Introductionmentioning
confidence: 99%